Small Incision Lenticule Extraction for Correction of Myopia and Myopic Astigmatism: First 24-Hour Outcomes - Taixiang Liu; Tingting Dan; Yan Luo (Journal of Ophthalmology)
Purpose. To observe the first 24-hour (h) outcomes of the small incision lenticule extraction procedure (SMILE) for myopia and myopic astigmatism. Methods. Fifty-three eyes (27 patients) scheduled for SMILE were followed immediately (0 h), 2, 4, 6, and 24 h after SMILE. Uncorrected visual acuity (UCVA), conjunctival congestion, pain level, and corneal edema, thickness, and densitometry were recorded. Results. At 2 h after SMILE, 15.1% of eyes had ≤0.1 LogMAR UCVA; this increased to 62.3%, 98.1%, and 100% at 4, 6, and 24 h, respectively. Some eyes (33.96%) had mild corneal edema immediately after surgery. No 6 h postoperative edema was observed. In the first 24 h after SMILE, corneal thickness gradually decreased. Postoperative corneal densitometry values were significantly higher than preoperative values but gradually decreased during the first postoperative 24 h. Conclusions. In the first postoperative 24 h, UCVA and corneal status (edema and densitometry) improved quickly.